The effect of different salting methods on the quality of salted barracuda fish (Sphyraena barracuda) in Barru Regency - Rajenah, Rajenah; Angreni, Husni; Karim, Mutemainna; Harianti, Harianti (Sangia Research Media and Publishing, 2023)
This study aimed to know the effect of salting methods with different concentrations on the quality and organoleptic value of salted barracuda fish (Sphyraena barracuda). This research was conducted from June to July 2020 at the Sumpang Binangae Fish Port, Mangempang Village, Barru Regency. The research method used was an experimental method with four treatments, namely treatment A (salting barracuda with 15% salt concentration), treatment B (salting barracuda with a dry method using 20% salt concentration), treatment C (salting barracuda with a wet method using 15% salt concentration), and treatment D (salting barracuda with a wet method using 20% salt concentration and soaked for six hours). Data analysis used the ANOVA test. The results showed that the highest average value of waer content in sample C was 28.16%. The highest average values of ash and salt content in sample B were 22.11% and 12.38%. The highest average ALT value in sample C was 1.1x104 colonies, while the highest average organoleptic value was in sample D 8.67. This study concludes that the salting of salted barracuda has a significant effect on water content, ash content, salt content, and ALT. The results of the ANOVA for the organoleptic value in terms of appearance, smell, texture, and taste had a significant effect while the organoleptic value of fungi had no significant affected.